Genomic and Computational Analysis of Novel SNPs in TNP1 Gene Promoter Region of Bos indicus Breeding Bulls - Kashif Hameed Anjum; Asif Nadeem; Maryam Javed; Hafiz Ishfaq Ahmad; Amjad Riaz; Wasim Shehzad; Jahanzaib Azhar; Muhammad Fahad Bhutta (Genetics Research)
Transition nuclear proteins (TNPs), the principal proteins identified in the condensing spermatids chromatin, have been found to play a key role in histone displacement and chromatin condensation during mammalian spermatogenesis. One such gene belonging to the TNP family called TNP1 gene is abundantly expressed in the regulation of spermatogenesis, and its sequence is remarkably well conserved among mammals. Genomic analysis, by sequencing and computational approach, was used to identify the novel polymorphisms and to evaluate the molecular regulation of TNP1 gene expression in Sahiwal cattle breeding bulls. DNA samples were sequenced to identify novel single nucleotide polymorphisms (SNPs) in the TNP1 gene. Modern computational tools were used to predict putative transcription factor binding in the TNP1 promoter and CpG islands in the TNP1 promoter region. In the TNP1 gene, four SNPs, three TATA boxes, and one CAAT box were identified. One CAAT box was discovered at 89 bp upstream of start site ATG. The computational analyses indicated that the polymorphisms inside the promoter sequence results in an added HNF-1 transcription factor binding site. In contrast, the other variations may remove the naturally occurring SRF transcription factor binding site. The CpG islands in the TNP1 promoter region were predicted to be absent by the MethPrimer program before and after SNP site mutations. These findings pave the way for more research into the TNP1 gene’s promoter activity and the links between these SNPs and reproductive attributes in the Sahiwal breeding bulls.